Analisis Pengaruh PDRB, Inflasi, Jumlah Penduduk terhadap Pendapatan Asli Daerah di Kabupaten Eks Karisidenan Pati Tahun 2012 - 2018 - Dimas Priyono; Herniwati Retno Handayani (Universitas Diponegoro, 2021)
Regional economic development is an important indicator for analyzing a growth in an area. In this case the local government and the community manage existing resources and form a partnership pattern between the private sector and local governments. This will create new jobs and stimulating the development of economic activity in the region. PAD as a regional revenue reflects the level of regional independence. The study aims to analyze the effect of GRDP, Inflation, Total Population on local revenue in Pati Ex-Residency using quantitative methods of secondary data from 2012 - 2018. Using panel data from cross section data of 5 districts time series data from 2012 to 2018 in the former Karisidenan Pati District the most suitable method is the Fixed Effect Model. The result shows that GDRP, Inflation, Total Population have a positive and significant effect on local revenue, Total Population has the highest influence. Simultaneous test results show that the variables of GRDP, Inflation, Total Population simultaneously have a significant effect on Regional Original Income. When these variables can be optimized, the economic activity in Pati Ex-Residency will develop well.